The impact of physiologic and non-physiologic delivery on the mother and neonate outcomes; a comparative study on the primi gravid mothers. - Maryam Khooshide; Tiba Mirzarahimi; Ghodrat Akhavan Akbari (Tehran University of Medical Sciences, 2015)
Objective:To compare the effect of the physiologic and facilitated labor on the mother and neonate outcomes in the prim gravid women referring to Arash Hospital. Materials and methods:This clinical trial study was performed on 200 low risk pregnant women referring to Arash Women's Hospital in 2012-2013. Mothers were divided into two groups of 100 patients using a simple random sampling method. The first group received the on-pregnancy and physiologic labor training and the second group was nominated for facilitated labor without training. The mother and neonate outcomes in these two delivery methods were then compared. Results:The rate of cesarean section in the physiologic group was significantly lower compared with the intervention group (p = 0.001). Also in the first stage of labor, VAS was measured to be noticeably lower in the physiologic group in comparison with the intervention group (p = 0.001), while the difference of VAS between the two studied groups was found not to be significant in the second stage of labor. In terms of duration of the labor and neonatal Apgar score two groups were not considerably different (p > 0.05). Moreover, the laceration rate in the physiologic group was determined to be noticeably higher as compared to the intervention group (p = 0.001). The groups were considerably different in terms of the vaginal bleeding and maternal satisfaction (p = 0.001). Conclusion: This study revealed the lower rate of cesarean section, abnormal vaginal bleeding and pain score in the physiologic group compared with the facilitated group. Moreover, mothers of the first group were more content with the labor process.